ESTIMATION OF SCALE ELASTICITIES AND PRICE FLEXIBILITIES OF MEAT AND FISH IN SAUDI ARABIA - M. Al-Mahish (Journal of Animal and Plant Sciences, 2020)
This paper applied the synthetic inverse demand model to estimate scale and price flexibilities of lamb, beef, chicken, and fish in Saudi Arabia. Model selection tests showed that the differential inverse AIDS model and the inverse CBS model provided the best fit for the data. The estimated own-price flexibilities for both models were negative and consistent with theory. Furthermore, the results revealed that a 1% increase in aggregate quantity of meat and fish decreased the normalized prices of fish and chicken by approximately 0.7% and 1.1%, respectively.
Keywords: Inverse Demand; Price Flexibility; Scale Elasticity; Meat; Fish